Análise automática de normas aplicada em projeto geométrico de superestrutura ferroviária - Romulo Luiz Pereira Ribeiro (2018)
Checking the conformity of a project with the normative texts that regulate it is generally done manually, using a variety of work resources, such as time and skilled labor. This study proposes the development of a methodology to perform computationally automated standards analysis in the geometric design of railway superstructure, and also proposes the implementation of this methodology in a computer system integrated to AutoCAD Civil 3D associated with BIM (Building Information Modeling) technology infrastructure. This system will be useful both for the professional responsible for the project and for the governmental entity responsible for the analysis and approval of the project, both will have access to the computational tool that will be used for the development of the project in a BIM environment, in which technical instructions, formulations and adjustments will be available at the moment of development and approval of the projects. The research is conducted by Design Science Research through the structure proposed by March and Storey (2008), which consists of identifying the problem, showing that there is no adequate solution, developing an artifact to solve the problem, evaluating the artifact produced and exposing of the practical and scientific contribution that research and artifact provide. The methodology developed for performing the automatic analysis of standards consists in comparing the values of the project parameters with the normative values and with values calculated through formulations established by the area literature. After the calculations, results reports are displayed so that the user can identify which parameters comply with the normative criteria and which parameters are in disagreement with the standards. The developed system was evaluated by performing a standards check on a 10 km stretch of the Centro-Atlântica Railway. The results demonstrate that the proposed method for automatic verification of standards is adequate for its purposes, providing fast and reliable checks, being able to be used for the revision and approval of new railway projects. This research contributes to the progress of the railway development objectives in Brazil and also represents progress in the development and application of BIM concepts in the construction of specific models for railway projects, where new methods and tools for automatic verification of standards, showing a new way of automating the process of development, verification and approval of railway projects with the application and benefits of new technologies.